PUBLIC POLICIES, YOUTH AND SOCIO-EDUCATIONAL SYSTEM: THE EXPERIENCE OF THE THEMATIC SECTORAL CHAMBER OF MATO GROSSO - Olivera, Raul Angel Carlos; Brito, Daniel Almeida; Pereira, Vanusa Batista; Mendo, Cesar David; Mendo, Cristina Teodoro de Melo; Fernandez, Rose Kelly dos Santos Martínez; Silva, José Renato de Oliveira; Dan, Evelin Mara Cáceres (Seven Editora, 2025)
The Economic Observatory is based on a Freirean concept of university extension. In this context, in partnership with the Legislative Assembly of the State of Mato Grosso, the institutionalization of the Thematic Sector Chamber (CST) was conceived: “The Prison System in the State of Mato Grosso: Socioeconomic and Institutional Aspects of Violence and Criminality”, composed of representatives of the Executive, Legislative, and Judicial branches, as well as non-governmental organizations. This article presents the trajectory, process, and results achieved by the CST, which adopted the Brainstorming methodology to encourage representatives of the Comprehensive Protection Network for Adolescents to contribute ideas in order to generate a broad list of problems and potential solutions. As a result, intersectoral policies for serving adolescents in conflict with the law were proposed and a diagnosis of the sports and leisure activities developed by the institutions was prepared. The findings indicated several needs and difficulties faced by public agents in dealing with adolescents. The importance of sports and leisure as educational practices in the formative process and the need to articulate specific policies aimed at this group were emphasized. It was also argued that such policies should take into account all social differences, not only adolescents deprived of liberty, but also other groups historically made invisible by the government. DOI: https://doi.org/10.56238/sevened2025.021-068